Lepromatous leprosy mimicking systemic lupus erithematosus: a case report (Medical Journal of Indonesia, 2019)
The clinical manifestations of leprosy are highly variable, and the disease is notorious for being “a great imitator” of several other conditions. Leprosy may manifest with a variety of phenomena resembling those of autoimmune diseases. Herein, we report a 33-year-old male presenting with wounds on his left leg and hyperpigmented skin lesions all over his body. Six years earlier, the patient was diagnosed with systemic lupus erythematosus (SLE). However, therapy for SLE did not control his symptoms; instead, the patient developed features of leprosy, such as anesthetic skin lesions, nerve enlargement, and tenderness. Tests for antinuclear antibodies and anti-double stranded DNA antibodies were negative. Slit-skin smear showed a bacterial index of 6+ and morphological index of 10 %. Lupus band test results were negative. Histological findings were compatible with lepromatous leprosy. The clinical and serological similarities between leprosy and SLE may lead to erroneous diagnosis. Thus, clinicians should be aware of this characteristic for correct diagnosis.